Influence of different operating conditions on centrifugal compressor surge control with active magnetic bearings. Issue 1 (1st January 2019) - Guan, Xudong; Zhou, Jin; Jin, Chaowu; Xu, Yuanping; Cui, Hengbin
ABSTRACT: The purpose of this paper is to study the surge control effects of centrifugal compressors with active magnetic bearings (AMBs) under several operating conditions. First, the working principle of the magnetic thrust bearing is introduced, and the tracking performance of the rotor under the low frequency is verified by experiments. Then, the Greitzer model of centrifugal compressor is established. The relationship between tip clearance and the performance of compressor is derived, and the proportional-integral-derivative surge controller is designed based on the mass flow feedback. Finally, the surge control platform of the centrifugal compressor with active magnetic bearings is set up, and the surge control experiment of the magnetic bearing system is carried out. The influence of different speeds and different throttle valve openings on surge control performance is analyzed. The experimental results illustrate that speed has little effect on surge control, and the different throttle valve opening sizes have a certain influence on surge. The surge controller designed in this paper has a good control effect on different throttle valve opening sizes. Thus, the magnetic thrust bearing is effective in surge control by adjusting the tip clearance of the compressor.